ANALISIS STRATEGI KOMUNIKASI PEMASARAN SMB TELKOM UNIVERSITY TAHUN 2015/2016 MELALUI MEDIA SOSIAL INSTAGRAM - Mayrisa Anggun Utami (Jurnal Sosioteknologi, 2016)
Marketing communications is something that must be implemented in company. Differentiation and development of the market that getting forward demanding company more wise in the conduct of marketing communications strategy. Currently many companies using social media as marketing communications media. Also Telkom University, as a universities based on ICT, Telkom University want to communicate messages by social media. One of the these social media is instagram. Instagram is the application of social media at smartphone and the function have almost the same as others social media, but the difference lies in the taking of photos and can share information on other users. This research aims to review and analyze the strategy of marketing communications SMB Telkom University in 2015/2016 throught instagram and to knows message strategy and media strategy used by Marketing Telkom University in marketing communication via Instagram. This research used qualitative descriptive method. This research found that there are several steps messages and strategies of media used by Marketing Telkom University in his marketing communications through instagram.